Analysis of Rear-End Collisions at Roundabout Approaches. Issue 1 (2016) - Burdett, Beau; Alsghan, Ibrahim; Chiu, Li-Hong; Bill, Andrea R.; Noyce, David A.
Roundabouts are common alternatives to stop- and signal-controlled intersections and have grown in popularity in response to the promise to reduce traffic crash severity at intersections. In Wisconsin, more than 300 roundabouts have been installed. Studies of these intersections have found a 38% reduction in fatal and injury crashes. However, a 12% overall increase also was found, and this finding is not unique to Wisconsin. An increase in less-serious crashes can lead to a negative public perception about roundabout benefits. The causes of rear-end collisions (a common type of low-severity crash) were examined. Four years of crash reports from 55 roundabouts were analyzed along with the geometric conditions of the roundabouts. The 16- to 24-year-old driver age group represented a significantly higher proportion of involvement in rear-end collisions than in total crashes across the state. Negative binomial models were created for roundabout approaches. For combined one-lane and multilane roundabout approaches, annual average daily traffic, sawtooth pavement markings, and high deflection angles were significantly correlated with an increase in the expected number of rear-end collisions, and wider entry was significantly correlated with a decrease in the expected number of rear-end collisions. For one-lane approaches, "Yield" pavement markings led to an expected reduction in crashes, as did the presence of horizontal curves within 250 feet of a roundabout. These findings reflect the complexity of driving at roundabout approaches, especially for younger drivers. Results also indicate the importance of proper pavement markings at approaches.